2007
DOI: 10.1369/jhc.7a7353.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fascin Expression in Human Embryonic, Fetal, and Normal Adult Tissue

Abstract: S U M M A R Y This study investigates the distribution of fascin in human embryonic, fetal, and normal adult tissues. Tissue microarray technology was used to perform immunohistochemical experiments on human embryos and fetuses at 4-22 weeks of gestation and adult specimens. Fascin was widely expressed in the nervous system. At 4 weeks of gestation, fascin was present in the neural tube. At 8-12 weeks of gestation, homogenous gene expression was seen in cells of the cerebellum and gastrointestinal tract. In la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 27 publications
4
91
0
Order By: Relevance
“…The cases were received between 1987 and 1997. The cases were selected to build tissue microarrays as described (28) and were included in this study only if a follow-up was obtained and clinical data were available. Mean age at surgery was 53 years (range , and 127 patients were male and 66 were female.…”
Section: Methodsmentioning
confidence: 99%
“…The cases were received between 1987 and 1997. The cases were selected to build tissue microarrays as described (28) and were included in this study only if a follow-up was obtained and clinical data were available. Mean age at surgery was 53 years (range , and 127 patients were male and 66 were female.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, it has been reported that fascin + tumor epithelium has strong invasiveness with poorer prognosis in various carcinomas, such as ovarian, breast, pancreas, lung, cutaneous, brain, gastrointestinal, thyroid, prostate, urothelial, intrahepatic cholangiocarcinoma and skin tumors (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The significance of epithelial fascin expression has been reported to be associated with invasiveness and metastasis, since it aids in cell migration and proliferation through increases in lamellipodial and filopodial cell protrusions (15).…”
Section: Epithelium -------------------------------------------------mentioning
confidence: 99%
“…In normal adult human tissues, fascin expression is restricted to neurons and DCs; both cell types have markedly large filopodia and are highly motile (11,13). Fascin expression in various neoplastic cells has also been investigated, and its expression has been reported to be associated with epithelial to mesenchymal progression and invasion of tumor cells as well as a clinically aggressive manifestation and poorer prognosis (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, to the best of our knowledge, immunohistochemical studies for the detection of fascin + mature DCs in thymoma have yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Fascin-1 is abundant early in development, especially in the central nervous system (CNS) and migrating cells, and is then downregulated as cells mature (De Arcangelis et al, 2004;Zhang et al, 2008;Zanet et al, 2009;Tang et al, 2010). In this paper, 'fascin' refers to the product of the Fascin-1 genes (FSCN1 in humans, MIM#602689; Fscn1 in mouse; and singed in Drosophila, FBgn0003447).…”
Section: Introductionmentioning
confidence: 99%